Inventarisasi dan Karakterisasi Jenis-Jenis Sagu (Metroxylon Spp) di Distrik Sentani Tengah dan Distrik Sentani Timur Kabupaten Jayapura Provinsi Papua - Yunus Monim; Frederik Luhulima; Dwiana Wasgito Purnomo (Fakultas Pertanian Universitas Papua, 2017)
This research aimed to inventory and characterize the types of sago from Central Sentani and East Sentani Districts, Jayapura regency, Papua province. This study was designed by using descriptive method with field survey technique. The result found that there were total of 36 sago types at Central Sentani and East Sentani Districts. The most sago types was found from Ifale and Yoboi villages for about 24 types. The less community understanding about the important of sago could results in the extinct of some sago types. External morphological character of sago may be used as differentiated key of sago at Sentani.